2016
DOI: 10.1016/j.exphem.2016.06.075
|View full text |Cite
|
Sign up to set email alerts
|

Defining the minimal factors required for erythropoiesis through direct lineage conversion

Abstract: SUMMARYErythroid cell commitment and differentiation proceed through activation of a lineage-restricted transcriptional network orchestrated by a group of well characterized genes. However, the minimal set of factors necessary for instructing red blood cell (RBC) development remains undefined. We employed a screen for transcription factors allowing direct lineage reprograming from fibroblasts to induced erythroid progenitors/precursors (iEPs). We show that Gata1, Tal1, Lmo2, and c-Myc (GTLM) can rapidly conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Interestingly that study also demonstrated that lentiviral transduction of BCL11A alone was sufficient to induce the expression of b2globin in the immortalized iPSCderived HiDEP-1 cell line because that cell lines had adult-like levels of KLF1 [52]. A recent study that added KLF1 to iEP cells showed adult-like globin [17]. The erythroid cells derived from the SFCi55 iPSC cell line used in this study have lower levels of KLF1 compared to differentiated adult CD34 1 cells (Fig.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Interestingly that study also demonstrated that lentiviral transduction of BCL11A alone was sufficient to induce the expression of b2globin in the immortalized iPSCderived HiDEP-1 cell line because that cell lines had adult-like levels of KLF1 [52]. A recent study that added KLF1 to iEP cells showed adult-like globin [17]. The erythroid cells derived from the SFCi55 iPSC cell line used in this study have lower levels of KLF1 compared to differentiated adult CD34 1 cells (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Current protocols to produce RBCs from hPSC have limitations because they generate a relatively low proportion of enucleated cells and express embryonic/foetal but not adult globin [6]. Forward programming using lineage specific transcription factors has been used to enhance the production of a number cell types from hPSCs including hematopoietic lineages [16,17,40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental validation is required to determine if the motifs uniquely enriched in specific classes control different enhancer states and whether multiple binding events are required for enhancers to transition from an inactive state to a functional state. However, there are examples of multiple TF binding events driving expression of the Hbb gene to facilitate cell fate transitions (Capellera-Garcia et al, 2016;Mitchell et al, 2012).…”
Section: Discussionmentioning
confidence: 99%